2020
DOI: 10.3889/oamjms.2020.5030
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oral Contraceptives use with Breast Cancer and Hormone Receptor Status in Iraqi Women

Abstract: BACKGROUND: Worldwide, there is a significant concern regarding the association of breast cancer risk and oral contraceptives use. Differences in demographical and pathological breast cancer characteristics in Iraqi patients have been reported compared to other western countries; however, studies addressing the risk of breast cancer among oral contraceptive users in Iraq and subsequent correlation with hormonal receptor status are lacking. AIM: The aim of the study was to evaluate association of breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In six patients without a history of using hormonal contraception, all experienced a decrease. Based on the duration of hormonal contraception use, 18 patients had a duration of use <5 years, with four patients (22%) experiencing an increase and 14 patients (78%) experiencing a decrease, and three patients with a history of contraceptive use [16].…”
Section: Discussionmentioning
confidence: 99%
“…In six patients without a history of using hormonal contraception, all experienced a decrease. Based on the duration of hormonal contraception use, 18 patients had a duration of use <5 years, with four patients (22%) experiencing an increase and 14 patients (78%) experiencing a decrease, and three patients with a history of contraceptive use [16].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to high levels of estrogen stands as one of the factors that can heighten the incidence of breast cancer risk, either causing permanent damage to breast tissue or triggering the presence of cancer cells within the ducts and lobules. The incidence of breast cancer is increased in individuals using menopausal hormone therapy [27] . The current study's results revealed a significantly higher frequency of postmenopausal status among females with localized breast cancer, with 56% being postmenopausal patients, 38% perimenopausal patients, and 6% premenopausal patients, as depicted in Figure 1.…”
Section: Menopausementioning
confidence: 99%